Il Grande Oriente d’Italia e l’educazione: l’azione delle logge nelle grandi città (1868–1925) - Xoccato, Demetrio (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2017)
The present paper focuses on the Italian Freemasonry’s engagement in the educational field. From 1868 to 1925, the lodges under the Grand Orient of Italy fostered and helped many educational establishments. The article considers the following three cities: Turin, Milan and Rome. These important urban centres were different but shared a large number of initiatives and a will to test new secular learning models (Boarding schools, institutes, evening classes and Popular Universities).